1993
DOI: 10.1016/0014-5793(93)81757-q
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin found in the archaebacterium Thermoplasma acidophilum

Abstract: Systematic N-terminal sequencing of the low molecular weight proteins from Thermoplasma acidophilum separated by two-dimensional polyacrylamide gel electrophoresis led to the discovery of a polypeptide with an apparent Mr of 4.5 kDa identical as its first 18 amino acid residues to human ubiquitin. The occurrence of ubiquitin and proteasomes in an archaebacterium strongly suggests that ATP ubiquitin-dependent proteolysis is a cellular function that developed early in evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 22 publications
(11 reference statements)
0
21
0
Order By: Relevance
“…At present, the putative posttranslational modification that leads to proteasome-mediated protein degradation in Archaea has not been defined. While some reports suggest the existence of ubiquitin in Archaea (275,300,473), no direct demonstration of archaeal ubiquitin has been provided, nor have analyses of archaeal genomes identified ubiquitin-encoding genes or genes encoding ubiquitin-transferring proteins. Stuctural studies, however, have revealed the existence of ar- (33,375).…”
Section: Protein Ubiquitinationmentioning
confidence: 99%
“…At present, the putative posttranslational modification that leads to proteasome-mediated protein degradation in Archaea has not been defined. While some reports suggest the existence of ubiquitin in Archaea (275,300,473), no direct demonstration of archaeal ubiquitin has been provided, nor have analyses of archaeal genomes identified ubiquitin-encoding genes or genes encoding ubiquitin-transferring proteins. Stuctural studies, however, have revealed the existence of ar- (33,375).…”
Section: Protein Ubiquitinationmentioning
confidence: 99%
“…Some, but not all, prokaryotes contain Ub (29). The bacterium E. coli lacks Ub but does have an N-end rule pathway ( (9).…”
Section: Figmentioning
confidence: 99%
“…Some, but not all, prokaryotes contain Ub (Wolf et al 1993). The bacterium E. coli lacks Ub but does have an N-end rule pathway (Fig.…”
Section: Figurementioning
confidence: 99%